Incidence and Risk of Fatal Vehicle Crashes Among Professional Drivers: A Population-Based Study in Taiwan - Tsai, Jui-Hsiu; Yang, Ya-Hui; Ho, Pei-Shan; Wu, Trong-Neng; Guo, Yue Leon; Chen, Pau-Chung; Chuang, Hung-Yi (Frontiers in Public Health, 2022)
Fatal vehicle crashes (FVCs) are among the leading causes of death worldwide. Professional drivers often drive under dangerous conditions; however, knowledge of the risk factors for FVCs among professional drivers remain scant. We investigated whether professional drivers have a higher risk of FVCs than non-professional drivers and sought to clarify potential risk factors for FVCs among professional drivers. We analyzed nationwide incidence rates of FVCs as preliminary data. Furthermore, by using these data, we created a 1:4 professionals/non-professionals preliminary study to compare with the risk factors between professional and non-professional drivers. In Taiwan, the average crude incidence rate of FVCs for 2003–2016 among professional drivers was 1.09 per 1,000 person-years; professional drivers had a higher percentage of FVCs than non-professional drivers among all motor vehicle crashes. In the 14-year preliminary study with frequency-matched non-professional drivers, the risk of FVCs among professional drivers was significantly associated with a previous history of involvement in motor vehicle crashes (adjustment odds ratio [OR] = 2.157; 95% confidence interval [CI], 1.896–2.453), previous history of benzodiazepine use (adjustment OR = 1.385; 95% CI, 1.215–1.579), and speeding (adjustment OR = 1.009; 95% CI, 1.006–1.013). The findings have value to policymakers seeking to curtail FVCs.